The Climate Change Policies of the Green Party of Aotearoa/New Zealand: An Eco-Socialist Analysis and Critical Evaluation - Roper, Brian (New Zealand Sociology, 2023)
Accelerating climate change and the ineffectiveness of governmental policy responses has led many to hope that Green parties will promote more effective policy measures. This article focuses on the Green Party of Aotearoa (GPA) which has maintained continuous parliamentary representation since 1996, receiving from 5.2 to 11% of the vote in national elections from 1999 to 2020. It has been a support partner in Labour-led governments following the 2017 and 2020 elections. Providing an account of how the GPA’s climate change policies have developed and shifted since the foundation of the party in 1990, it seeks to answer the following question: What are the strengths and weaknesses of the intellectual outlook and climate change policies of the GPA with respect to likely effectiveness in reducing carbon emissions and combatting climate change? The critical analysis required to answer this question operates on two levels. With respect to critical policy analysis, the focus is on the scale, scope, sequencing and pace of change. At a more fundamental level, the article explores the extent to which the GPA’s intellectual outlook and policy programme constitute an adequate response to the problems generated by neoliberalism, capitalism, class, and the disproportionate influence of business over government. It concludes that although the GPA’s climate change policies are better than those of the other parliamentary parties, these policies are problematic at both levels.